Penerapan Model Pembelajaran Make A Match untuk Meningkatkan Hasil Belajar Bahasa Indonesia Siswa SD - Mersty E. Rindengan (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to improve student learning outcomes in the fourth grade Indonesian language subject at SD GMIM 02 Manado by applying the Make A Match Type Cooperative Learning Model. This research was conducted with reference to the Classroom Action research method with 2 cycles. This classroom action research uses 4 stages, namely planning, implementing / acting, observing and reflecting. This data was collected through observation and analysis of the results of the fourth grade students' test with a total of 20 students consisting of 12 boys and 8 girls. This data is obtained through increasing the abilities and skills of students in the learning process and student learning outcomes. From the learning outcome data obtained by researchers at SD GMIM 02 Manado in grade IV, analyzed by calculating the percentage of student learning outcomes completeness, different results were obtained where in cycle I student learning outcomes only reached 59%, while in cycle II the results student learning reaches 87%. So in this study it can be concluded that the application of the make a match cooperative learning model can improve Indonesian learning outcomes with material about understanding the contents of the story in class IV SD GMIM 02 Manado. It is hoped that the application of the make a match type of cooperative learning model can help teachers, especially students, to be more motivated and able to work together in learning, especially in understanding the subject matter.